Experiences with older adults using art therapy - Rojas Borboa, Grace Marlene (UNIVERSIDAD DE SONORA, 2021)
This article shows an experience of systematizing a project using art therapy in a center for older adults with neurodegenerative diseases. A program of 12 sessions is developed with around 10 participants using elements of dance, theater and visual arts with music accompaniment to generate creative working conditions, both individually and collectively. It was possible to observe how, from being not very sociable people, with insecurities and deterioration of their faculties, group integration, cohesion, decision-making and improvement in their physical abilities were achieved. The entire process carried out in order to improve the project for future interventions is recorded.